THE ROLE OF FACEBOOK AS A PUBLIC COMMUNICATION MEDIA FOR THE COMMUNICATION AND INFORMATICS SERVICE OF SIKKA REGENCY The Role of Facebook as a Public Relations Media - Maria Ernesti; Yonas Klemens Gregorius Dori Gobang; Markus Kristian Retu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines the role of Facebook as a public communication medium utilized by the Department of Communication and Informatics of Sikka Regency. The research aims to analyze how the social media platform is employed to disseminate information, foster interaction with the public, and enhance transparency and accountability of local government. Using a qualitative approach, the study collects data through in-depth interviews, observation, and content analysis. The findings reveal that Facebook serves as an effective tool for public information dissemination, fostering two-way communication, and increasing public participation. However, challenges such as technological infrastructure limitations and low digital literacy need to be addressed to optimize the use of this social media platform. This study examines the role of Facebook as a public communication medium utilized by the Department of Communication and Informatics of Sikka Regency. This study aims to analyze how the social media platform is utilized to disseminate information, foster interaction with the public, and enhance transparency and accountability of local government. Using a qualitative approach, this study collects data through in-depth interviews, observation, and content analysis. The results show that Facebook serves as an effective tool for disseminating public information, fostering two-way dialogue, and increasing public participation. However, there are challenges such as limited technological infrastructure and digital literacy in society that need to be overcome so that the use of social media is more optimal